Older patients’ participation in team meetings—A phenomenological study from the nurses’ perspective - Lindberg, Elisabeth (Co-Action Publishing, 2013)
Although the importance of patient participation is acknowledged in today’s healthcare, many challenges remain before patient participation can become an integral part of care provision. The ward round has traditionally been the forum for crucial decisions about patient care, but often with limited possibilities for patient participation. As part of the process of improving patient participation, the round in the present study has been replaced by a team meeting (TM) to which the patient has been invited. The aim of this study is to highlight nurses’ experiences of older patients’ participation in TMs. The research process was guided by the principles of phenomenological reflective life world research. Data were collected in a Swedish hospital, in a ward specializing in older patients. Nine nurses, who had invited and planned for a patient to participate in TMs and/or had experienced TMs in which patients participated, were interviewed. The essential meaning of patient participation in the TM, as experienced by the nurses, is that patient participation can be supported by a safe relationship in which the patient can make his or her voice heard. Participation is challenged by the patients’ vulnerability and by the subordinated role assigned to the patient. The essential meaning is further described by its constituents: “the need for a guide,” “patient participation challenged by structures,” and “creating space for the whole human being.” In conclusion, the nurse plays a core role in guiding the patient in an unfamiliar situation. The meaning of patient participation in the TM needs to be discussed by professionals so that the patient perspective is present.